REACTIVE PLASMACYTOSIS: A DIAGNOSTIC CONUNDRUM IN ACUTE MYELOID LEUKAEMIA - Hameed, Mehreen; Raziq, Fazle (Journal of Ayub Medical College Abbottabad, 2021)
Bone-marrow being a home to various kinds of normal hematopoietic cells, sometime becomes overcrowded by abnormal cell population in malignancies like in acute myeloid leukaemia. One such dilemma in diagnosis betides when two abnormal cell populations in bone-marrow occur at the same time. A prime example is when reactive plasmacytosis in bone-marrow eventuate in relation with acute myeloid leukaemia (AML). Due to scarce amount of such cases reported, it is imperative to understand the difference between reactive plasmacytosis which arises after induction of chemotherapy and the one which is diagnosed along with AML, during initial diagnosis due to other causes, like infections and IL-6 production by the leukemic blast population. To substantiate these erstwhile arguments, the brief case history of a 45 years old female patient diagnosed with acute myeloid leukaemia with coincident reactive plasmacytosis having no previous history of chemotherapy is presented along with review of past published literature.